HEALTH INSURANCE IS A ROAD TO FINANCIAL HEAVEN”- A STUDY ON PERCEPTION AND SATISFACTION OF CUSTOMERS TOWARDS HEALTH INSURANCE. - Begum, Dilshad (ShodhKosh: Journal of Visual and Performing Arts, 2024)
INTRODUCTION: Nature is uncertain and unpredictable. The same is true with the life of an individual which is surrounded by risks and uncertainties in this volatile world. Any kind of misfortune may lead from minor to serious injuries or even loss of life. Diseases too never knock our doors to enter our body. Money will never ever be able to buy life or cure diseases till the existence of this world but to cope up with hard times in our life and life of our near and dear ones when we leave for heavenly abode. Health insurance is one of the important approaches that can help in boosting universal healthcare coverage through improved healthcare utilization and financial protection. The objectives of this review is to identify various interventions implemented in Karnataka to promote perception and satisfaction level of health insurance towards health insurance by the resident of Karnataka population.